Ekstraksi dan Uji Stabilitas Zat Warna Alami dari Bayam Merah (Alternanthera amoena Voss): Extraction and Stabilization of Natural Dyes from Red Spinach (Alternanthera amoena Voss) - Khairuddin; Joy Noldy Baciang; Indriani; Nov Irmawati Inda (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Research on the extraction and stability test of natural dye from red spinach (Alternanthera amoena Voss) has been carried out. This study aims to determine the effect of pH and length of sun exposure on the stability of the dye from red spinach. Extraction using the maceration method with ethanol solvent and measurement using a UV-Vis spectrophotometer. Stability testing is carried out at pH 2-5 and sun exposure for 1-4 hours using a dark and light container. The results obtained, at pH 2 and pH 3, anthocyanins were more stable, compared to pH 4 and 5 which had greater color degradation. In exposure to sunlight, dark containers with a degradation percentage of 31.70% were better than clear containers with a percentage of 48.78%. Keywords: Anthocyanin, red spinach, natural dyes stability.